PENGEMBANGAN MEDIA PEMBELAJARAN FOCUSKY BERBASIS LEARNING CYCLE 5E PADA MATERI SISTEM PENCERNAAN MANUSIA DI SMA NEGERI 2 LUWU - sukmawati syam; Gita olivia (Jurnal Biogenerasi, 2022)
This study aims to develop a focusky learning media based on the 5E learning cycle on the human digestive system material at SMA Negeri 2 Luwu. This research is an R&D (Research and Development) research with ADDIE development research design which consists of five stages, namely analysis (analyze), design (design), development (development), implementation (implementation) and evaluation (evaluation). The subjects of this study were students of class IX IPA 5 SMA Negeri 2 Luwu selected by simple random sampling technique. Data collection techniques using validation sheets and questionnaires. Furthermore, the data were analyzed by validation and practicality tests. The results showed that: (1) The validity analysis was declared very valid based on the assessment of the media expert validator with a validity percentage of 87.5% and the material expert validator with a validity percentage of 97.5%. (2) The practicality analysis is stated to be very practical based on the teacher's response and after using the application with a score of 95% and the student response with a score of 87.5%. This means that the focusky learning media based on the 5E learning cycle that has been developed can be used in digestive system.